Women’s Empowerment in Local and Global Fiction: From Toba Beyond - tarigan, Karisma erikson; Simamora, Rosa Maria (English Education Department at FKIP Nommensen University, 2024)
This study explores women's empowerment in literature, focusing on the interplay between tradition and modernity across different cultural contexts. Employing comparative literary analysis, this research examines Lucy by Jamaica Kincaid and Mangalua by Idris Pasaribu. The methodology involves thematic and narrative analysis, where thematic analysis identifies key motifs related to empowerment, resistance, and gender roles, while narrative analysis examines how each character's story arc reflects broader societal norms. Through these analyses, the study highlights how each protagonist navigates societal expectations and challenges gender norms within traditional and modern frameworks. Findings indicate that both novels use women’s empowerment as a lens to critique and reshape cultural expectations, offering insights into gender roles across varied societies. The study concludes with recommendations for further research on cross-cultural gender narratives, acknowledges the limitations of focusing on only two novels, and suggests broader literary comparisons for future studies.